Sublingual delivery of chondroitin sulfate conjugated tapentadol loaded nanovesicles for the treatment of osteoarthritis. (2nd January 2021) - Bishnoi, Mamta; Jain, Ankit; Singla, Yashpaul; Shrivastava, Birendra
Abstract: Recent treatment approaches of osteoarthritis (OA) face a number of obstacles due to the progressive multitude of pain generators, nociceptive mechanisms, first pass mechanism, less efficacy and compromised safety. The present study was aimed to bring a novel approach for the effective management of OA, by developing sublingual targeted nanovesicles (NVs) bearing tapentadol HCl (TAP), surface modified with chondroitin sulfate (CS). Optimized nontargeted nanovesicle formulation (MB-NV) was developed by an ultrasound method, characterized as spherical in shape, nanometric in size (around 150 nm) with narrow size distribution (polydispersity index <0.5), and good entrapment efficiency (around 50%). MB-NV conjugated with CS which was confirmed by IR and 1 H NMR spectroscopy. C-MB-NV showed improved pharmacokinetics parameters i.e. increased t 1/2 (9.7 h), AUC (159.725 μg/mL*h), and MRT (14.99 h) of TAP than nontargeted formulation and plain drug soln. C-MB-NV in in vitro release studies proved sustained drug release pattern for more than 24 h following Higuchi model kinetics with Fickian diffusion ( n ≤ 0.5).Targeted nanovesicles exhibited an improved bioavailability and enhanced analgesic activity in a disease-induced Wistar rat model which indicated the superior targeting potential of C-MB-NV exploiting CD44 receptors as mediators, overexpressed at the affected joints in the OA model. It could be a propitious approach to accustomed therapies for methodical and efficient management in advanced OA therapy.